THE FIRST EXPERIENCE OF BALLOON-ASSISTED ENTEROSCOPY - V. M. DURLESHTER; S. A. GABRIEL; V. Y. DYNKO; V. S. KRUSHELNICKIY; A. Y. GUCHETL; A. V. AVAKIMYAN (Кубанский научный медицинский вестник, 2017)
The article presents first experience of balloon-assisted enteroscopy (BAE) for one year (from December 2015 to December 2016). The total number of patients was 19. In this group performed 28 balloon-assisted enteroscopy. Of these, 12 patients underwent oral BAE, 2 transanal and 14 combined. Diagnostic BAE was 18 and 10 operating. The article analyzes the main and concomitant diseases in this group of patients, the number and types of is operating and diagnostic interventions, their effectiveness. Analyzed further management of patients in the identification of surgical pathology. We present the most interesting clinical cases.